Intermediate Written Chinese Practice Essentials : Read and Write Mandarin Chinese as the Chinese Do - Cornelius C. Kubler (USA : Tuttle Publishing, 2015)
Annotation 'Intermediate Written Chinese Practice Essentials' offers a wealth of carefully-designed exercises and activities to help you develop every aspect of your reading and writing ability
Keywords: Chinese characters Study and teaching; Chinese language Textbooks for foreign speakers English; Chinese language